Influence of management styles and job stress on job performance of records management personnel in selected ministries in Rivers state civil service, Nigeria (2018)
Records management personnel contribute immensely to the attainment of civil services goals. Job performance is of high relevance in civil service and for individuals alike. Moreover, high performing personnel get promoted and rewarded. Job performance of records management personnel does not occur arbitrarily or in a vacuum; their level of job performance is dependent on management styles, job stress and other motivational factors that are germane to increasing their performance. However, the chaotic state of records registries and records centres associated with difficulties in accessing information resources in selected ministries informed the decision to undertake this study to investigate management styles and job stress as factors influencing job performance of records management personnel in selected ministries in Rivers State Civil Service, Nigeria. The descriptive survey design of correlational type was used for the study. The population of the study was 315 records management personnel in the two ministries selected for the study. The total enumeration method was adopted to study the entire 315 records management personnel due to the small size of the population. The questionnaire tagged 'Management Styles, Job Stress and Job performance Questionnaire' was the instrument for data collection. The instrument was pre-tested by administering 30 copies to records management personnel in Rivers State Ministry of Environment which was not one of the ministries studied. The result showed that significant positive relationship existed between autocratic management style and job performance of records management personnel, while management styles and job stress did not significantly and relatively influence job performance of records management personnel in selected ministries in Rivers State Civil Service, Nigeria. Finally, a case was made for the adoption of the management style that is goal-oriented and capable of enhancing the job performance of records management personnel in the civil service.